GAMBARAN TINGKAT PENGETAHUAN SWAMEDIKASI PENGOBATAN DISMINOR PADA SANTRI TAKHASUS DI PONDOK PESANTREN HAJAR ASWAD YOGYAKARTA - Windy Aulina; Zaenal Fanani; Emma Jayanti Besan (Nusantara Hasana Journal, 2025)
Dysmenorrhea is a medical term used to describe pain experienced during menstruation, particularly in the lower abdominal area, occurring before or during the menstrual period. This condition is commonly known as menstrual pain or menstrual cramps. Limited understanding of dysmenorrhea self-medication is influenced by inadequate access to health information, especially regarding menstrual pain management. Therefore, this study was conducted to describe the level of knowledge of takhasus female students at Hajar Aswad Islamic Boarding School, Yogyakarta, regarding dysmenorrhea self-medication. This research employed a purposive sampling method, in which respondents were selected based on specific criteria. The sample size was determined using the Slovin formula. Data were collected through a questionnaire, and data analysis was conducted using a paired sample t-test with the assistance of Microsoft Excel and SPSS software. The results showed that after receiving educational intervention, there was a significant increase in students’ knowledge, with most respondents achieving a good knowledge category. The paired sample t-test results indicated a significant difference between pre-test and post-test scores (p-value = 0.000), demonstrating that educational intervention significantly improved students’ knowledge regarding dysmenorrhea self-medication.